1997
DOI: 10.1017/s1074070800007756
|View full text |Cite
|
Sign up to set email alerts
|

Economic Analysis of Environmental Benefits of Integrated Pest Management

Abstract: Public support for integrated pest management (IPM) is derived in part from concerns over food safety and the environment, yet few studies have assessed the economic value of health and environmental benefits of IPM. An approach is suggested for such an assessment and applied to the Virginia peanut IPM program. Effects of IPM on environmental risks posed by pesticides are assessed and society's willingness to pay to reduce those risks is estimated. The annual environmental benefits of the peanut IPM program ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
45
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(46 citation statements)
references
References 7 publications
1
45
0
Order By: Relevance
“…Considerably fewer studies address the ecological dimension of pesticide risk (see, e.g. Higley and Wintersteen, 1992;Mullen et al, 1997;Lohr and Higley, 1999;Foster and Mourato, 2000;Brethour and Weersink, 2001;Cuyno et al, 2001). …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Considerably fewer studies address the ecological dimension of pesticide risk (see, e.g. Higley and Wintersteen, 1992;Mullen et al, 1997;Lohr and Higley, 1999;Foster and Mourato, 2000;Brethour and Weersink, 2001;Cuyno et al, 2001). …”
mentioning
confidence: 99%
“…Higley and Wintersteen (1992), Mullen et al (1997), and Brethour and Weersink (2001) extend the focus of the pesticide risk literature by including the valuation of changes in integrated pesticide risk management on the environment in addition to considering acute and chronic human toxicity for farmers. 3 Their environmental categories include ground and surface water, aquatic species, avian species, mammals, and arthropods.…”
mentioning
confidence: 99%
“…Significantly fewer studies address the ecological dimension of agrochemical risk (see, e.g. Higley and Wintersteen, 1992;Mullen et al, 1997;Lohr et al, 1999;Foster and Mourato, 2000;Brethour and Weersink, 2001;Cuyno et al, 2001;Travisi and Nijkamp, 2004). But what can we learn from the abundance of results in the literature?…”
Section: Stated Preferencementioning
confidence: 99%
“…Examples of previous studies using CV methods for pesticide risk valuation can be found in Higley and Wintersteen (1992); Bubzy et al (1995); Mullen et al (1997); Fu et al, (1999); Brethour and Weersink (2001); Cuyno et al (2001); Wilson (2002). Recently, Foster and Mourato (2000) and Schou et al (2002) have applied Contingent Ranking techniques to value multiple pesticide impacts, while several examples of Conjoint Analysis -applied to the valuation of various pesticide risks for consumers-can be found in Baker and Crosbie (1993), Eom (1994) and Baker (1999).…”
Section: Introductionmentioning
confidence: 99%